Analysis of the Jak Lingko Program as a Transportation in Jakarta - Yudhistira Al Adha; Dede Sri Kartini; Novie Indrawati Sagita (Journal of Public Representative and Society Provision, 2026)
This study aims to analyze the Jak Lingko program as a means of transportation in Jakarta. The research method used is qualitative. The subjects of this study were stakeholders of the Jak Lingko policy program in Jakarta. The research instruments used as supporting tools or technical instruments were interview guidelines, several photo files, audio files, related documents, and tools such as computers/laptops, digital cameras, mobile phones, flash drives, stationery, and vehicles as transportation for researchers in conducting research. Data collection techniques in this study were literature studies, field studies through observation, and interviews. The results of this study are as follows: The importance of transportation integration in Jakarta stems from the high level of traffic congestion that has never been resolved, along with the level of pollution produced by transportation facilities.